2020
DOI: 10.34142/hsr.2020.06.03.07
|View full text |Cite
|
Sign up to set email alerts
|

Influence of swimming on sensory functioning, quality of life and behavior of children with autism

Abstract: <p><strong>Aim: </strong>to establish the influence of swimming as a means of adaptive physical education on behavior, emotional state, sensory, motor coordination and quality of life of children with autism spectrum disorders (ASD).</p><p><strong>Material and methods</strong>. Three children with autism who were swimming were examined. Research methods: pedagogical observations, pedagogical experiment, method of expert evaluations, questionnaires.</p><p>&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It also highlighted a greater capacity for achievement and self-esteem of children with ASD (44). In fact, hydrotherapy represents a potential practice that would improve the relational, emotional and social integration aspects in individuals affected by ASD (48). In fact, during swimming, all muscles in the body are activated, afferent nerve stimuli to the CNS come from the proprioceptors of muscle fibers, and after processing, the CNS directs the impulses through the efferent fibers to the muscles.…”
Section: Swimmingmentioning
confidence: 99%
“…It also highlighted a greater capacity for achievement and self-esteem of children with ASD (44). In fact, hydrotherapy represents a potential practice that would improve the relational, emotional and social integration aspects in individuals affected by ASD (48). In fact, during swimming, all muscles in the body are activated, afferent nerve stimuli to the CNS come from the proprioceptors of muscle fibers, and after processing, the CNS directs the impulses through the efferent fibers to the muscles.…”
Section: Swimmingmentioning
confidence: 99%
“…Musiyenko, O. V conducted teaching observations and experiments on autistic children swimming. The results indicated that for children with autism, individual swimming courses can be recommended as an effective means of adaptive swimming education [5]. Although the above research has great scientific and social value, there is a lack of exploration of swimming courses for contemporary young college students.…”
Section: Introductionmentioning
confidence: 99%
“… 28 Swimming combines the multisensory stimulation of an enriched environment with the motor stimulation of physical activity. 29 It is one of the most effective exercise programs to promote neurodevelopment and neuroplasticity. 30 Proper weight-bearing swimming exercise can have extremely important effects on the nervous system, skeletal muscle and cardiorespiratory function.…”
Section: Introductionmentioning
confidence: 99%